Baseline carcinoembryonic antigen (CEA) serum levels predict bevacizumab-based treatment response in metastatic colorectal cancer - Prager, Gerald W (Cancer Sci, 2014)
Carcinoembryonic antigen (CEA) affects tumorigenesis by enhancing tumor cell survival and by inducing tumor angiogenesis. This study aimed to evaluate baseline CEA serum levels to predict bevacizumab-based therapy effect and survival in patients with metastatic colorectal cancer (mCRC). Two hundred and ninety eight mCRC patients receiving chemotherapy plus either bevacizumab or cetuximab were analyzed in a retrospective study. Disease control (DC), progression-free survival (PFS), and overall survival were assessed and related to pretreatment CEA serum levels. Patients with baseline CEA serum levels below the statistical median of 26.8 ng/mL (group I) were compared with patients with higher CEA levels (group II). The cetuximab-based treatment cohort was analyzed for specificity assessment of CEA to predict the anti-vascular endothelial growth factor effect in mCRC. Baseline CEA serum levels inversely correlated with therapeutic response in patients receiving bevacizumab-based treatment (disease control rate, 84% vs 60%), inversely correlated with median PFS leading to a median PFS benefit of 2.1 months for patients in group I when compared with group II, as well as inversely correlated with median overall survival (37.5 months vs 21.4 months). In an independent cohort of 129 patients treated with cetuximab-based therapy, no association of therapeutic response or PFS with CEA serum levels was found. As expected, baseline CEA levels were prognostic for mCRC. These data give first evidence that baseline serum CEA levels might constitute an important predictor for the efficacy of first-line bevacizumab-based therapy in patients with mCRC. Previously, we found that CEA induces angiogenesis independent of VEGF. The data presented here now give first evidence that baseline serum CEA levels in patients might constitute an important predictor for the efficacy of first-line bevacizumab-based therapy for metastatic colorectal cancer.